Pengembangan Modul Berbasis Penelitian Pencegahan P. berghei pada Mus musculus terhadap Berpikir Kritis Mahasiswa - Maya Wahyunarti; Ridwan Yahya; Agus Sundaryono (University of Bengkulu, 2019)
Abstract[Module Development Based on P. berghei Prevention Research in Musculus on Student Critical Thinking]. This study aims to develop learning module based on the research of prevent the occurrence P. berghei bacterial infection and as well as to determine students' critical thinking skills against learning process by modules. This study is Research and Development with 4D design (define, design, development, and desimination). The results of the study found prevention of Plasmodium behergei infection from% inhibitors of erythrocytes at each dose. The dosage used in this study was a dose of 0.014 g / kgbb, 0.028 g / kgbb, 0.056 g / kgbb. The dose of 0.014 g / kg has an 9,24 % inhibitor, a dose of 0.028 g / kgbb has a 9.93% inhibitor, the dose of 0.056 g / kgbb has a 6.61% inhibitor. So the dose of 0.028 g / kgbb is the dose that most reduces the risk of P.berghei infection Mus musculus. In this study the critical thinking students of Semester 6 Chemistry University of Bengkulu classically are good category with a score of 63.13. This percentage is divided in some indicators, the indicator focus to the question is 67.92 value on the Critical criteria, considering the source can be trusted or not in the critically enough criteria with a value of 59.58, conclude by induction and consider the results of induction with a value of 64, 58 with critical criteria and identify assumptions of getting 63.13 values with critical criteria.Keyword: Module; J. Multifida; P. Berghei; Mus musculus; Critical Thinking.(Received November 19, 2018; Accepted April 15, 2019; Published June 18, 2019)AbstrakPenelitian ini bertujuan mengembangkan modul pembelajaran berbasis penelitian pencegahan infeksi Plasmodium berghei terhadap kemampuan berpikir kritis mahasiswa. Penelitian ini adalah penelitian Research and Development dengan desain penelitian 4D (define, design, development, and desimination). Hasil penelitian didapatkan pencegahan infeksi Plasmodium behergei dari % penghambat pada eritrosit pada setiap dosis. Dosis pada penelitian digunakan dosis 0,014 g/kgbb, 0,028 g/kgbb, 0,056 g/kgbb. Dosis 0,014 g/kgbb memiliki %penghambat 9,24 % , dosis 0,028 g/kgbb mimiliki %penghambat 9,93 %, dosis 0,056 g/kgbb memiliki %penghambat 6,61%. Jadi dosis 0,028 g/kgbb merupakan dosis yang paling mengurangi resiko terinfeksi P.bergehei pada mencit. Pada penelitian berpikir kritis mahasiswa pendidikan Kimia Semester 6 Universitas Bengkulu secara klasikal berada pada kategori baik dengan nilai 63,13. Persentase ini dibagi dalam beberapa indikator yakni indikator memfokuskan pertanyaan berada pada kriteria Kritis dengan nilai 67,92, mempertimbangkan apakah sumber dapat dipercaya atau tidak berada pada kriteria cukup kritis dengan nilai 59,58, menyimpulkan dengan cara induksi dan mempertimbangkan hasil induksi dengan nilai 64,58 dengan kriteria kritis dan mengidentifikasikan asumsi mendapatkan nilai 63,13 dengan kriteria kritis.Kata kunci: Modul; J. Multifida; P. Berghei; Mus musculus; Berpikir Kritis.